PENGARUH VARIASI SUHU DAN WAKTU TERHADAP NILAI RENDEMEN DAN KADAR FLAVONOID TOTAL EKSTRAK DAUN JINTEN (Coleus amboinicus L.) DENGAN METODE EKSTRAKSI ULTRASONIK - Firdaus Tandya Hermawan (2023)
Cumin leaf (Coleus amboinicus L.) is one of the plants that contains flavonoids and widely found in Indonesia. Flavonoids are secondary metabolite compounds that have many benefits including antimicrobial, antioxidant, anti viral and can prevent cancer. To take metabolite compounds in plants, an extraction process is needed. In the extraction process, various factors can affect the extraction results, one of which is temperature and length of extraction time. The purpose of this study was to determine the effect of temperature (45,60,75oC) and time (10,15,20 min) variations on the yield value and total flavonoid levels of cumin leaf extract using ultrasonic extraction. The ultrasonic method is an effective and efficient method in the extraction process to produce maximum extracts. Based on the results of the one-way ANOVA variations with yield values obtained p values < 0.05 so that temperature influences yield values, while time variations do not significantly affect the yield value because p values > 0.05. The highest yield value in cumin leaf extract was obtained at a temperature of 75oC with a time of 20 minutes of 23.35%, while the total flavonoid content value from cumin leaf extraction at a temperature of 45oC (p > 0.05) with a time of 20 minutes (p < 0.05) which was 16 mg QE / gr.